Elevated expression of genes assigned to NF-κB and apoptotic pathways in human periodontal ligament fibroblasts following mechanical stretch - Ritter-Rodriguez, Nina; Wörtche, Eva; Steinberg, Thorsten; Kohl, Annette; Komposch, Gerda; Tomakidi, Pascal (Cell & tissue research, 2007)
There is growing evidence that apoptosis involves the nuclear transcription factor NF-κB in conjunction with related genes. However, in the context of mechanical orthodontic forces, force-sensing target genes assigned to pathways of NF-κB and apoptosis have not been fully characterised. To contribute to the identification of putative target genes, we used cDNA arrays specific for NF-κB and apoptotic pathways and analysed elevated gene expression in primary human periodontal ligament fibroblasts (PDL-F) after a 6 h application of mechanical force. Among several identified genes (including several caspases), interleukin-1β (IL-1β) and NF-κB displayed significantly higher expression on the NF-κB array, whereas higher expression was obtained for BCL2-antagonist of cell death (BAD), member 6 of the TNF-receptor superfamily (FAS) and CASP2 and RIPK1 domain-containing adaptor with death domain (CRADD) on the apoptosis array. Based on a defined cut-off level of a more than 1.5-fold higher expression, this significance in elevated gene expression was corroborated by reverse transcription/polymerase chain reaction (RT-PCR). Here, semi-quantitative (sq) PCR revealed a more pronounced elevation of mRNA gene expression in PDL-F after 6 h of stretch, when compared with 12 h. Moreover, the elevation after 6 h as observed by sq-PCR was convergent with quantitative PCR (q-PCR). q-PCR yielded levels of 5.8-fold higher relative gene expression for IL-1β and 1.7-fold for NF-κB, whereas that computed for BAD indicated a 5.2-fold, for CRADD a 2.1-fold and for FAS a 2.0-fold higher expression. The data obtained from the expression analysis thus indicate a stretch-induced transcriptional elevation of genes assigned to the NF-κB and apoptotic pathways. This elevation may render them target candidates for being addressed by mechanical orthodontic forces.
Gesehen am 10.02.2021